565. Risk of COVID-19 Among Healthcare Workers After Launch of Vaccination Campaign at an Academic Medical Center. (4th December 2021) - Navalkele, Bhagyashri D; Lucar, Jose; Brock, James B; Parham, Jason
Abstract: Background: Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 virus affected healthcare workers (HCWs) adding additional burden on staffing shortages. COVID-19 vaccination (mRNA 1273 and BNT162b2) has been shown to protect against severe disease, death and reduced risk of asymptomatic infection and transmission from fully vaccinated individuals. Here, we present the impact of COVID-19 vaccination (CoVac) on risk of developing COVID-19 based on test results among unvaccinated and vaccinated HCWs. Methods: Our academic medical center with 11, 785 HCWs on its Jackson campus initiated non-mandatory CoVac among HCWs with BNT162b2 on December 16, 2020. Individuals ≥ 2 weeks after 1st dose of vaccine were defined as partially vaccinated and those ≥2 weeks from 2nd dose of vaccine were defined as fully vaccinated. Per facility policy, all symptomatic HCWs (irrespective of vaccination status) were recommended to undergo SARS-CoV-2 RT-PCR testing. Asymptomatic HCWs were also tested upon household exposure, however, this policy was changed on March 9 th 2021 to allow fully vaccinated asymptomatic HCWs to work without need for quarantine or testing. Universal masking policy among HCWs remained effective at our center during study period. Results: Between the launch of COVID-19 vaccination on December 16, 2020 and April 30, 2021, 5, 855 HCWs received one dose of vaccine, and 5, 687 received both doses. A total of 1, 329 unique HCWs underwent COVID-19 testing between January 4, 2021 and April 30, 2021. Of those, 217 (16.3%) tested positive for SARS-CoV-2 infection; 204 were unvaccinated, 7 were partially vaccinated, and 6 were fully vaccinated (figure 1). Of the 6 fully vaccinated employees, 1 was asymptomatic (testing for travel purposes), 4 had mild symptoms, and one elderly employee required hospitalization with oxygen supplementation and had a complete recovery. No facility outbreaks were reported related to asymptomatic, work exposed, fully vaccinated HCWs. Unvaccinated healthcare workers were more likely to test positive for SARS-CoV-2 compared to partially and fully vaccinated healthcare workers. Conclusion: COVID-19 vaccination protected HCWs by reducing risk for developing COVID-19. Vaccinating healthcare workers is a crucial infection prevention measure to reduce disease burden, avoid staffing shortages and create a safe environment in the healthcare facility to prevent transmission to other staff and at-risk patients. Disclosures: All Authors : No reported disclosures